PENGARUH KEMASAN DAN WAKTU PENYIMPANAN TERHADAP KEMAMPUAN BERKECAMBAH BENIH MENTIMUN - U. Sumpena (Universitas Wahid Hasyim, 2012)
SUMPENA.2011.To Determine the effect of Packing and Storage Method on the Viability of Cucumber Seed. Following reports poor Cucumber seed germination from farmers who had been sent seed, a laboratory experiment was conducted to determine the effect of storage period and packing method on the viability of four cucumber variety. The experiment was conducted at LEHRI from January 2010 to December2010. A Split Plot Design with three replications was used with packing method as the main plot and storage period as the subplot. After 6 mount Cucumber seed germination (82%) was significantly higher when stored at room temperature in vacuum packed alumunium foil sachets, than all other packing methods. The percentage of Cucumber seed which around 60% after 4 mount to 21% and 10% after 6 mounts respectively. When first tested, the Venus variety exhibited significantly lower germination (63%) than the other varietys which ranged from 86-98%. Key word; Storage, packing, cucumber seed, viability.